Lack of lipid accumulation in two species of chalcidoid wasps with secondarily evolved phytophagy. Issue 6 (27th March 2022) - Lammers, Mark; Kraaijeveld, Ken; Ellers, Jacintha
Abstract: Stable co‐evolutionary relationships between species may result in the loss of autonomous synthesis of essential nutrients when these can be obtained from the ecological partner. Parasitoid insects obtain most of their nutrients from their host, and many lineages do not increase their adult lipid reserves even when feeding on a surplus of sugars. Several clades within the parasitoid Hymenoptera have lost the parasitoid lifestyle and switched to either a predatory or a phytophagous lifestyle. Here, we test whether adult lipid accumulation is reactivated in two species that independently evolved a phytophagous lifestyle from parasitoid ancestors. The larvae of Megastigmus aculeatus (Swederus) (Hymenoptera: Chalcidoidea: Torymidae) and Bruchophagus platypterus (Walker) (Hymenoptera: Chalcidoidea: Eurytomidae) obligatorily feed on seeds of specific plants. Seeds of wild host plants were collected and the emerging wasps were tested for the lipid accumulation phenotype using whole‐body diethyl ether extraction. Both species had significantly reduced lipid content after 1 week ad libitum access to sugars compared to the lipid content at emergence, indicating a lack or negligible level of lipogenesis. Therefore, the secondary switch to phytophagy was not associated with recovery of lipid accumulation in these species. We discuss these results in relation to the lipid content of the host seeds and the reversibility of the lipid accumulation phenotype. We infer that the close relationship among seed‐feeding insects and their hosts allows the seed‐feeders to rely on a diet with predictable lipid quantities which relaxes the need for autonomous lipid synthesis. Abstract : The majority of parasitoids phenotypically lack lipid accumulation as adults. There are repeated reversals from parasitoid to phytophagous lifestyle. Seed‐feeding wasps originated several times; they feed on seeds as larvae but have free‐living adults like their ancestors. We tested two species of seed‐feeding wasps from independent lineages: Megastigmus aculeatus and Bruchophagus platypterus (Hymenoptera: Chalcidoidea: Torymidae, Eurytomidae). Adults of both species did not accumulate lipids. Thus, secondary loss of the parasitic lifestyle does not concur with a regain of lipid accumulation.